Inventing new rights: precarity and the recognition of the productive dimension of life. (1st December 2016) - ,; ,
Abstract : Marked by the centrality of communicational, affective and relational aspects in direct value generation, cognitive capitalism is characterised by ambivalences that are expressed in new forms of control and exploitation and by the way that it has overcome several distinctions that shaped Fordist industrial labour. This article aims to observe how, in the transition to cognitive capitalism, precarity is constituted as an existential condition of contemporary labour. Furthermore, it seeks to demonstrate how this reality, while introducing risks and vulnerabilities, creates a terrain for new possibilities of resistance and invention.